2006
DOI: 10.1159/000096314
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Protection against Homologous Drift Variants of Influenza A and B after Vaccination with Split Vaccine

Abstract: The aim of this serological study was to demonstrate the extent to which antibodies react against subsequent drift variants, after vaccination with split vaccine (FluarixTM). Antibody titers have been determined by hemagglutination inhibition test (HI) against different influenza A and B drift variants in sera from three past multicenter trials. Individuals of two different age groups, i.e. 18–60 years and above 60 years, were enrolled. Vaccine components influenza A/H1N1 and influenza B of Fluarix<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…The assays that were performed to test the presence of the anti-influenza antibodies were hemagglutination inhibition tests. In these types of assays, a requirement of 40 HI units defines a protective antibody [13]; thus, these cross-reactive antibodies might provide protective functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assays that were performed to test the presence of the anti-influenza antibodies were hemagglutination inhibition tests. In these types of assays, a requirement of 40 HI units defines a protective antibody [13]; thus, these cross-reactive antibodies might provide protective functions.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody cross-reactivity among various influenza virus strains has been detected in several studies following immunization with influenza vaccines [13-15]. Recently, antibodies that recognize different influenza viruses have been discovered [16].…”
Section: Introductionmentioning
confidence: 99%
“…The potential for vaccine to stimulate antibody protection across B lineages requires further evaluation and may be dependent upon age and/or prior antigenic experience with both B lineages. (1)(2)(3)(4)(5) Over time, antigenic variation (antigenic drift) of strains occurs within an influenza A subtype or B lineage. Despite this antigenic drift, some cross-protection among strains belonging to the same A subtype or B lineage is expected, depending on how different the strains are.…”
Section: I2 Backgroundmentioning
confidence: 99%
“…(89) After careful review, NACI concludes that egg-allergic individuals may be vaccinated against influenza using TIV, without a prior influenza vaccine skin test, based on an assessment of risk for a severe allergic reaction to guide the method of vaccination. (NACI recommendation Grade A) 2 Because of the lack of data, the use of FluMist® in eggallergic persons is not recommended at this time. However, ovalbumin concentrations in FluMist® are documented to be very low and a study is currently underway to assess the use of FluMist® in egg-allergic persons.…”
Section: Persons With Egg Allergymentioning
confidence: 99%
“…Naturally acquired serum bactericidal antibodies could provide protection from infection with homologous strains, but provide little protection against heterologous strains[33, 34]. Subbarao noted that immunity to influenza infection by antigenic variants is reduced with a greater degree of antigenic variation[3537]. Walsh indicated that the implications of strain variation on vaccine design for RSV remain unclear[38].…”
Section: B Common Themesmentioning
confidence: 99%